Incretin-based therapy: renal effects - Anton Ivanovich Korbut; Vadim Valerievich Klimontov (Сахарный диабет)
Glucagon like peptide-1 (GLP-1) analogues and dipeptidyl peptidase-4 (DPP-4) inhibitors are new classes of hypoglycemic agents with numerous pleiotropic effects. The review summarises data about the influence of GLP-1 analogues and DPP-4 inhibitors on structural and functional changes in diabetic kidneys. Growing evidence indicates that the kidney is one of the loci of the effects and degradation of GLP-1. The potency of the effects of GLP-1 in diabetic kidneys can be reduced by decrease in GLP-1 receptor expression or enhancement of GLP-1 degradation. In experimental models of diabetic nephropathy and non-diabetic renal injury, GLP-1 analogues and DPP-4 inhibitors slow the development of kidney fibrosis and prevent the decline of kidney function. The mechanisms of protective effect include hyperglycaemia reduction, enhancement of sodium excretion, suppression of inflammatory and fibrogenic signalling pathways, reduction of oxidative stress and apoptosis in the kidneys. In clinical studies, the urinary albumin excretion reduction rate while using the GLP-1 analogue and DPP-4 inhibitor treatment was demonstrated in patients with type 2 diabetes. Long-term impact of these agents on renal function in diabetes needs further investigations.